1997
DOI: 10.1136/ip.3.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Sibling power: influence of older siblings' persuasive appeals on younger siblings' judgements about risk taking behaviours.

Abstract: Objectives-Although many injuries happen when school age children are away from home and in the company of other children, we know surprisingly little about interpersonal influences on children's risk taking decisions. The aim of the present study was to examine the influence of older siblings' persuasive appeals on young children's decisions about engaging in behaviours that could threaten their physical safety. Methods-Forty same sex sibling pairs participated. Children were shown drawings of play scenes (bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 7 publications
6
25
1
1
Order By: Relevance
“…The authors found that friend persuasion had a significant ability to alter children's choices, so long as it was a situation where the child would not be completely abandoning his or her own, original convictions. In addition, the study found that the number of persuasive appeals made by friends was just as important in influencing change as the message or content of the appeal (Christensen and Morrongiello, 1997). These findings suggest that negative peer influences may be countered by instilling children with strong convictions about the importance of seat belt use.…”
Section: Peersmentioning
confidence: 88%
See 1 more Smart Citation
“…The authors found that friend persuasion had a significant ability to alter children's choices, so long as it was a situation where the child would not be completely abandoning his or her own, original convictions. In addition, the study found that the number of persuasive appeals made by friends was just as important in influencing change as the message or content of the appeal (Christensen and Morrongiello, 1997). These findings suggest that negative peer influences may be countered by instilling children with strong convictions about the importance of seat belt use.…”
Section: Peersmentioning
confidence: 88%
“…Researchers suggest that because of the relationship between parental use and children's use, successful interventions could target either parent or child, but preferably both (Russell et al, 1994). Children are also likely to be influenced by the behaviors of their older siblings (Morrongiello and Bradley, 1997).…”
Section: Demographic and Socioeconomic Characteristics And Their Effementioning
confidence: 99%
“…When Morrongiello and Bradley13 studied children persuading their siblings how best to cross a hypothetical river, they found that boys tended to use arguments that focused on having fun, while girls framed their discussions around safety. Most of the subjects in that study felt that their parents would only have preferred them to take the safer route because they did not understand ‘how good [the child was] at the activity depicted’ 13.…”
Section: Discussionmentioning
confidence: 99%
“…Há evidências de que crianças abaixo de 6 anos somente são capazes de se lembrar de menos da metade das regras de segurança da casa (por exemplo: não correr com tesouras ou não tocar em panelas quentes), mas o mais importante é que o conhecimento não tem relação com a redução efetiva de injúrias 87 . Um estudo mostrou que uma relação positiva entre irmãos é preditiva de escolhas de comportamentos mais seguros por escolares; tanto irmãos quanto irmãs mais velhos eram capazes de persuadir os mais jovens a evitar riscos, mas os meninos apelavam mais para brincadeiras, enquanto as meninas para o juízo 88 .…”
Section: O Microambiente: Fatores Interpessoaisunclassified